The Implementation of Intelligibility-Based Pronunciation Instruction on a Pre-Sessional Eap Course in the Uk - Hodgetts, John (Research in Language, 2021)
Pre-sessional EAP access courses for learners of English intending to study on undergraduate or postgraduate courses in the UK are faced with particular challenges in incorporating meaningful suprasegmental pronunciation instruction into their programmes. This research examines the pronunciation goals of teachers, course leaders, and learners on a ten week UK pre-sessional access course, particularly with regard to suprasegmental instruction, how these goals are reflected in pronunciation assessment, and how teacher goals are informed by their attitudes and beliefs. A mixed methods approach, including direct observation and semi-structured interviews, is employed to address the area of enquiry. Results derived from course documents and a semi-structured interview show a lack of clarity of course goals. Although there is a general emphasis on suprasegmental rather than segmental instruction, in semi-structured interviews teachers report a lack of course goals. Assessment and practice do not always adhere to a goal of intelligibility, and support for teachers, in terms of the materials and how they might be exploited seems limited.